Effect of Mobile-Based Video Teaching Method on Students Learning Outcome on Female Catheterization Among Nursing Students at Two Schools in Enugu, Nigeria (African Journal of Biomedical Research, 2024)
This study compared mobile video instruction to face-to-face demonstrations in nursing practicum outcomes. Using quasi-experimental design, two nursing student groups were studied: UNTH-SON received mobile video instruction, while BS-SON had face-to-face demonstrations. Each group consisted of a randomly selected sample of 56 students (n=112). Prior to the intervention, a pre-test evaluated baseline skills, with the intervention group receiving a 30-minute video tutorial accessible on handheld electronic devices for three weeks, and the control group receiving twice-weekly 30-minute face-to-face sessions for the same duration. A post-test, conducted 21 days post-intervention, utilized a 39-item OSCE checklist with content validity of 0.902 and test-retest reliability of 0.817. Data were subjected to descriptive and inferential analysis (Student t-test and Fisher’s exact test) at a 5% significance level. Baseline skill assessment revealed the mobile video group's mean score at 16.54 (5.46), with 82.1% performing poorly, compared to the face-to-face group's mean score of 21.82 (6.72), with 64.3% performing poorly (p < 0.001). Post-intervention, the mobile video group scored 32.73 (5.49), with only 3.6% performing poorly, while the face-to-face group scored 33.23 (6.89), with 5.4% performing poorly (p = 0.627). Mobile video-based instruction exhibited a 42% higher effectiveness than face-to-face instruction, with a mean difference of 16.19 versus 11.41 (Effect Ratio 1.41). However, post-test scores showed no significant difference (p = 0.672). In conclusion, video-based teaching is effective for instructing basic nursing students in female urinary catheterization during educational practicum, especially when face-to-face demonstrations are impractical